Otolaryngologist's role in the diagnosis of amyotrophic lateral sclerosis. Issue 2 (23rd February 2021) - Costa, Joana Borges; Pereira, Diogo; Duarte, Delfim; Viana, Miguel
Abstract : Amyotrophic lateral sclerosis (ALS) is a progressive and late-onset fatal neurodegenerative disease characterised by selective death of motor neurons. The aetiology of ALS is still unknown and it is extremely heterogeneous in genetics and clinical presentation, being the respiratory failure the usual cause of death. We describe a case of a 61-year-old male patient referred to the otolaryngology consultation for a 6-month history of progressive solid dysphagia and dysphonia. The patient presented several voice alterations such as a dysarthric speech with hypernasal voice which evoked the hypothesis of a neuromuscular disease. That patient was observed by a neurologist and was submitted to an electromyography that confirmed the ALS diagnosis. This case highlights the key role of otolaryngologists in the diagnosis of ALS, in a way that many patients with a bulbar ALS form are initially studied by an otolaryngologist.